INOVASI OLAHAN KERIPIK KELAPA SEBAGAI STRATEGI PEMBERDAYAAN EKONOMI BERBASIS PRODUK LOKAL DI DESA LOYOK - Tira, Hendry; Junanda, Lalu Riko; Ananda, Brigita Haura; Delia, Valentina; Susetyo, Muhammad Rakha Putra; Hariyanto, Satria Putra; Alhamida, Herlina; Wahab, Alvina Oktavia; Agustina, Mutia; Cahyaningsih, Anjuri; Kartika, Cindy Angelia (Jurnal Bakti Nusa, 2025)
The coconut chip innovation program in Loyok Village, Sikur District, East Lombok, was implemented to optimize the utilization of abundant coconut plantation produce into high-value-added products. The goal of this activity was to improve community skills in coconut processing, promote economic independence, and create new business opportunities based on local potential. Activities included observing village potential, testing product formulations, training in coconut chip production for women in the Family Welfare Movement (PKK), and mentoring on packaging and marketing strategies. The program's results demonstrated improved community skills in coconut processing, awareness of the added value of local products, and expanded market access, including through social media and online platforms. Impacts include increased product selling prices, entrepreneurial motivation, the creation of new jobs, and strengthening family finances. Supporting factors for success include the availability of raw materials, active community involvement, and support from the village and the University of Mataram Community Service Program (KKN PMD) team. However, challenges such as limited capital, production equipment, and digital marketing skills still need to be overcome.